The Impact of Discovery Learning with Interactive Fraction Board Media on Fourth-Grade Students' Mathematical Engagement - Firnanda, Nabila; Indianasari, Indianasari (Papanda Publisher, 2025)
Elementary students frequently struggle with fraction concepts due to their abstract nature, resulting in passive learning behaviors and limited engagement. This study examined the effect of the Discovery Learning model assisted by interactive fraction board media on fourth-grade students' learning activity in fraction instruction. A pre-experimental design with One Group Pretest-Posttest configuration was employed at SD Negeri 01 Trans Bangsa Negara. Eleven fourth-grade students participated using saturated sampling technique. Learning activity was measured through structured observation sheets assessing participation, enthusiasm, interaction, and perseverance dimensions. The intervention implemented six-step Discovery Learning process combined with interactive fraction board media allowing physical manipulation of fraction representations. Data analysis utilized descriptive statistics to examine changes in learning activity scores between pretest and posttest conditions. Significant improvements in learning activity were observed following the intervention. Mean scores increased from 2.45 (pretest) to 4.18 (posttest), representing a 1.73-point improvement. The percentage of students in